On the Influence of foreign players on the success of football clubs - Royuela, V.; Gásquez, R. (Journal of Sports Economics, 2019)
This article analyzes whether having more foreign players influences the performance of football clubs. We do so by comparing a cross section of close to 1,000 football clubs all over the world. We find that, on average, those clubs in leagues with more foreign players display better results in the world rankings. Nevertheless, within each league, where all clubs have the same regulations, having more foreign players has no effect. In the end, when all clubs have the same possibilities for importing better players from abroad, what matters is the financial power to choose the better ones.